Analysis of the Effect of Corporate Governance Mechanism, Company Size and Leverage on the Integrity of Financial Statements - Fajar Imam Wahyudi; Hari Setiyawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The number of cases of manipulation financial statements that have occurred so far has encouraged all parties to make us aware of the importance of a financial report with integrity, namely a report that has reliability. Accounting information should be relevant because this information will be used for decision making, In addition to being objective, information is independent if it is unaffected by factors that could compromise its impartiality. The objective of this study is to investigate and assess the impact of “Institutional Ownership, Independent Commissioner, Audit Committee, Company Size, and Leverage on the Integrity of Financial Statements”. This type of research is quantitative and this research is a causal study with a population of 48 mining companies listed on the Indonesia Stock Exchange for the 2015-2019 period, there are 25 companies that are the research sample, so the number of samples during the 5-year research period is 113 samples with sampling technique carried out based on purposive sampling,It was decided to employ the multiple linear analysis method and the commen effect approach as the research analysis  model in this study. The study's findings show that Institutional Ownership, Independent Commissioner, Audit Committee, and Company Size have little impact on the Integrity of Financial Statements, but Leverage has a significant beneficial influence